SPIRITUAL TRANSFORMATION HEALING FOR CHILDREN WITH AUTISM AT RUMAH AUTIS DEPOK, INDONESIA - Ayuningtyas, Fitria; Genilo, Jude William (al-Balagh : Jurnal Dakwah dan Komunikasi, 2022)
Autism can be described as a severe neurobiological developmental disorder with early onset, causing problems in communicating and dealing with other people or their environment. Experts are still debating, whether autism should be listed as a disease. This research was conducted to find out the Spiritual Transformation Healing that was applied at Rumah Autis Depok. This research used ethnography of communication through the SPEAKING Grid. This research indicated that Quran therapy had a significant impact on children with autism. Quran therapy might be able to develop expected behaviors, such as controlling emotion, especially tantrums and meltdowns, for children with autism. Rumah Autis Depok applied Quran therapy since the opening of this branch (on February 14, 2009), as a part of spiritual transformation healing for families of children with autism.